IMPROVING REGENERATION IN THE TOOTH EXTRACTION AREA CAUSED BY ORTHOPEDIC PROBLEMS THROUGH PLASMA THERAPY (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Orthopedic complications—such as improper prosthetic loading, traumatic occlusion, or worn-out orthopedic constructions—can lead to tooth extraction, slowing the regeneration process in the extraction site, increasing bone resorption, and delaying soft tissue epithelialization. This article analyzes the scientific basis, clinical efficacy, and observed outcomes of plasma therapy (PRP/PRF) in enhancing alveolar bone and soft tissue regeneration. The fibrin matrix in PRF sustains the release of growth factors for 7–14 days, thereby accelerating angiogenesis, osteogenesis, and fibroblast proliferation. Numerous clinical studies have shown that patients treated with PRP/PRF maintain 30–40% more bone volume, and epithelialization occurs 3–5 days earlier. Plasma therapy is recommended as an effective biotechnology for significantly optimizing regeneration in tooth extractions with an orthopedic origin. For this study, we conducted research on 16 patients and compared the results.